2017
DOI: 10.1002/micr.30171
|View full text |Cite
|
Sign up to set email alerts
|

Anterior intercostal artery perforator flap in immediate breast reconstruction: Anatomical study and clinical application

Abstract: Based on this anatomical and clinical study, we found AICAP flap has a consistent vascularization with good perforators. And moreover, it is suitable for partial breast reconstruction (quadrantectomy) and does not appear to negatively impact patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 25 publications
0
43
0
Order By: Relevance
“…Other potential advantages include avoiding a mastectomy and providing skin cover for reconstruction if needed. Although reported surgical and aesthetic outcomes have been encouraging, these are limited to few centers routinely performing these procedures [13][14][15][16][17][18]. In collaboration with three other centers, we set up a multicenter prospective database and report on surgical outcomes in patients who underwent BCS and partial breast reconstruction using ICAP flaps.…”
Section: Introductionmentioning
confidence: 99%
“…Other potential advantages include avoiding a mastectomy and providing skin cover for reconstruction if needed. Although reported surgical and aesthetic outcomes have been encouraging, these are limited to few centers routinely performing these procedures [13][14][15][16][17][18]. In collaboration with three other centers, we set up a multicenter prospective database and report on surgical outcomes in patients who underwent BCS and partial breast reconstruction using ICAP flaps.…”
Section: Introductionmentioning
confidence: 99%
“…AICAP flaps are based on perforators originating from the rectus abdominis or oblique segment of the intercostal artery. 8 , 10 Cadaveric studies 11 and radiological studies 7 , 12 have demonstrated reliable and consistent location of perforator arteries.…”
Section: Discussionmentioning
confidence: 93%
“…AICAP flaps have been described in a V-Y or propeller fashion for the correction of small defects 13 ; they are especially useful in lower pole reconstructions for which other volume displacement or replacement techniques are challenging. 7 , 8 , 13 AICAP flaps have been shown to produce excellent cosmetic outcomes in immediate breast reconstruction. 7 The proposed technique allows larger defects to be reconstructed due to recruitment of larger volumes of tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chest wall perforator flaps (L-TAP and Li-CAP) can also be used as complete autologous flap reconstruction following mastectomy and was first described by Losken and Hamdi in 2009 [19,20]. This is a safe reconstruction option in the high-risk candidates, such as smokers, raised BMI, diabetics, or in patients where implant or complex autologous reconstructions are relatively contraindicated due to post-operative radiotherapy (Figures 20 and 21).…”
Section: Breast Cancer and Surgerymentioning
confidence: 99%